PEMANFAATAN BATANG PISANG (Musa sp.) SEBAGAI BAHAN BAKU PAPAN SERAT DENGAN PERLAKUAN TERMO-MEKANIS - Lis Nurrani (Jurnal Penelitian Hasil Hutan, 2012)
Agricultural waste materials are utilized an alternative raw material to substitute wood. This study aimed to explore the potential of banana stem as a fiberboard raw material, from its phrysical and mechanical properties. Separations of fibres was undertaken through thermo-mechanical treatment with temperature variation of 60°C, 80°C and 100°C, and the addition of adhesive 4% and 0% of fibre dry weight. Mat forming was accomplished with wet process, using bydrolic press and het press at a temperature of 185°C, pressure of 50 kg) cm³ for about 10 minutes. Results showed that pulp yield was 35,76% with physical and mechanical properties of board comply with the requirement of FAO1966 and JIS A 5908-2003, however, water absorption was very bigh. Treatment using adhesive 4% did not give any impact on improving the quality of board. Boiling temperature treatment provides a positive influence. The best quality fiberboard was obtained from boiling temperature of 100°C.